On data reduction methods for volcanic tremor characterization: the 2012 eruption of Copahue volcano, Southern Andes - Melchor, Iván (2020)
Fil: Melchor, Iván. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.